Filosofía, ciencias sociales, pobreza mundial - Cohen, Joshua (2011)
In this article, Joshua Cohen critically asseses one of the main claims that\nThomas Pogge defends in World Poverty and Human Rights. According to this thesis, that\nCohen calls Strong Thesis, most of the global poverty problem could be eliminated through\nminor modifications in the global order that would entail at most slight reductions in the\nincomes of the affluent. Cohen subjects this thesis to strict scientific scrutiny and concludes\nthat it is unwarranted by available evidence and argument. In the course of his argumentation,\nhe discusses other claims by Pogge such as the idea that the citizens of rich countries\nharm the poor, and he reflects on the connections between political philosophy and social\nsciences and the spirit that should govern our investigations concerning global poverty